Phytochemical screening, in vitro and in silico antibacterial investigation of Elaeocarpus ganitrus extract - Cicilia Novi Primiani; Weka Sidha Bhagawan; Pujiati Pujiati; Dewi Ratih Tirto Sari (Biota, 2024)
This study evaluated phytochemical composition, and in vitro and in silico antibacterial activity of Elaeocarpus ganitrus extract. Elaeocarpus ganitrus leaves, seed and fruit powder were extracted with absolute ethanol. Then, the extract was identified phytochemical compounds qualitatively and evaluated the antibacterial activity through in vitro against Staphylococcus aureus and E. coli. Molecular docking was conducted to evaluate the antibacterial mechanism of Elaeocarpus ganitrus extract. Elaeocarpus ganitrus leaves, seeds, and fruits extract presented positive tannin, saponin, cardiac glycoside, quinone, steroids, terpenoids, and anthocyanins. In vitro analysis performed Elaeocarpus ganitrus leaves strong inhibited Staphylococcus aureus growth and medium inhibition against E. coli. structure activity relationship revealed 14 of 72 compounds have high antibacterial activities. molecular docking of 7 compounds showed inhibition activity of D-alanin ligase of Staphylococcus aureus. Those compounds blocked the activity of D-alanine ligase at inhibitor sites of enzyme, and might be disrupted the cell wall synthesis. In conclusion, Elaeocarpus ganitrus contained several phytochemical compounds and has antibacterial activity both in vitro and in silico investigation.